Character Education Through The Center Method at Al Biruni School - Ahmad Yani (AWLADY : Jurnal Pendidikan Anak, 2022)
AbstractThe central method is the concept of learning through play which can be used as a means of instilling the values of character education from an early age. This method touches all aspects of life, including attitudes and behavior (character). The center itself is an abstract container where the teacher provides many series of activities for children to play. There are seven centers that are used as a means of character development, namely: Beam Center, Large Role Play Center, Small Role Play Center, Imtaq Center, Art Center, Preparation Center, and Natural Materials Center. Through activities in each center, the character of students is built. The characters that are built include; quality, respect, honesty, discipline, responsibility, diligent, humble, positive thinking, clean, friendly, affectionate, patient, sincere, solemn, grateful, istiqomah, taqwa, qanaah. Through these 18 attitudes, children's curiosity is also built, and stimulated so that children are smart and love learning. The type of research used in this research is qualitative with analytical descriptive methods or research that is supported by data obtained from field research. The subject of this research is the process of learning the central method in an effort to build the character of students. The data collection techniques used the methods of observation, interviews, documentation, and literature studies.